2001
DOI: 10.3189/172756501781832520
|View full text |Cite
|
Sign up to set email alerts
|

Glacier–volcano interactions deduced by SAR interferometry

Abstract: Glacier-surface displacements produced by geothermal and volcanic activity beneath Vatnajökull ice cap in Iceland are described by field surveys of the surface topography combined with interferograms acquired from repeat-pass synthetic aperture radar images. A simple ice-flow model serves well to confirm the basic interpretation of the observations. The observations cover the period October 1996–January 1999 and comprise: (a) the ice-flow field during the infilling of the depressions created by the subglacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…(Björnsson et al, 2001), (cf. Haeberli, 1983;Walder and Driedger, 1995) (1.4) Breaching of thermokarst and supraglacial lakes On ice-rich permafrost or stagnant glacier ice.…”
Section: Remote Sensing Selected Remote Sensing Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Björnsson et al, 2001), (cf. Haeberli, 1983;Walder and Driedger, 1995) (1.4) Breaching of thermokarst and supraglacial lakes On ice-rich permafrost or stagnant glacier ice.…”
Section: Remote Sensing Selected Remote Sensing Applicationsmentioning
confidence: 99%
“…Björnsson et al, 2001). However, strictly speaking this technique does track three-dimensional terrain surface shifts rather than elevation changes at fixed positions.…”
Section: Terrain Elevation Changes (Dtm Differences)mentioning
confidence: 99%
See 1 more Smart Citation
“…In Iceland, for instance, where active volcanoes are closely related to glacial activity, it has been shown that both geological and geo-environmental systems have strong relationships (Sigmundsson, 1991;Sigvaldason, 2000;Björnsson et al, 2001;Maclennan et al, 2002). At a small time scale, active geothermal systems at ice-capped volcanoes can enhance icemelt, especially at the base of glaciers (Björnsson, 1998), sometimes generating catastrophic floods associated with eruptions, that are known as jökulhlaups (Matthews & Clague, 1993), and also the main type of lahars produced in southern Chile (Moreno, 1993;Naranjo & Moreno, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vatnajökull overlies part of the eastern volcanic zone, encompassing the large volcanoes Hamarinn, Bárdarbunga and Grímsvötn (Björnsson and Einarsson, 1990). As part of the Grímsvötn field, the Skaftá basin is geothermally influenced and seismically active (Björnsson, 1977(Björnsson, , 1988(Björnsson, , 2002Björnsson et al, 2001;Björnsson and Einarsson, 1990).…”
Section: Study Areamentioning
confidence: 99%